The use of large-scale X-ray computed tomography for the evaluation of damaged structural elements from an old timber bridge. Issue 6 (2nd November 2022) - Björngrim, Niclas; Myronycheva, Olena; Fjellström, Per-Anders
ABSTRACT: This paper shows how timber structures in our cultural heritage can be evaluated by large-scale X-ray computed tomography (CT) to supplement visual inspection and conventional strength and biological degradation tests. Approx. 25 year old preservative-impregnated timber beams from a nearly 300-year-old timber bridge were replaced due to severe degradation. The condemned beams were examined by CT scanning, and three-point bending and decay tests were performed. The CT imaging gave a good overview of the internal structure of the beams, and features such as rot, nails and cracking could easily be detected and quantified. The CT images indicate that mild-steel nails from the decking of the bridge were the main cause of subsequent degradation by rot fungus. The load at breakage and the modulus of elasticity (MOE) values of the condemned beams were approx. half those of the undamaged reference beam. Large-scale CT scanning is a powerful tool for the non-destructive inspection of timber members in historical structures.